Biosorpsi Kadmium pada Leacheate TPA Gunung Tugel Menggunakan Biomassa Sargassum cinereum - Slamet Santoso; Sri Lestari; Dwi Sunu Windyartini (Majalah Ilmiah Biologi BIOSFERA: A Scientific Journal, 2010)
Leachate is liquid originated from organic waste. The substance consists of dissolved and suspended materials as a result of decomposition process by microorganisms. Leachate is waste consist of organic and high heavy metal. To manage leachate, heavy metal should be reduced by biosorption. Biosorption is heavy metal adsorbtion by inactive or death organism. The aims of the research were to examine the contact time, Sargassum cinereum biomass, combination of contact time and S. cinereum biomass to adsorb cadmium from the leachate. The experiments were based on Completely Randomized Design (CRD) with Spilt Plot Design. The treatments included contact time of Sargassum cinereum with leachate as main plot and S. cinereum biomass as sub plot. Contact time of S. cinereum with leachate consisted of three levels i.e., 1, 2 and 3 hours while S. cinereum biomass consisted of four levels, i.e., 200, 300, 400 and 500 mg. Data obtained were analyzed by analysis of variance (ANOVA) and followed by High Significant Difference (HSD) test. The results showed that S. cinereum biomass can adsorp cadmium from leachate. The level of adsorption of heavy metal was different in each treatment depending on contact time and S. cinereum biomass. The contact time of 3 hours was the optimum length in adsorping cadmium (39.168%) and 400 mg S. cinereum biomass was optimum amount in adsorping cadmium (38.936%). Combination of contact time 3 hours and 400 mg S. cinereum biomass was optimum treatment in adsorping cadmium (42.289%) from the leachate.